2020
DOI: 10.1371/journal.pone.0219874
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making flexibility in New Caledonian crows, young children and adult humans in a multi-dimensional tool-use task

Abstract: The ability to make profitable decisions in natural foraging contexts may be influenced by an additional requirement of tool-use, due to increased levels of relational complexity and additional work-effort imposed by tool-use, compared with simply choosing between an immediate and delayed food item. We examined the flexibility for making the most profitable decisions in a multi-dimensional tool-use task, involving different apparatuses, tools and rewards of varying quality, in 3-5-year-old children, adult huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…The ability to flexibly combine information in a domain-general manner 43 , when combined with playfulness and neophilic exploration of the environment, may be an important driver of technical innovations in kea and other species 44 , 45 . These results therefore support recent claims that tool use, including tooling, arises not only from the evolution of specialized physical cognition 46 49 , but can be innovated, when ecologically necessary, by species with sufficiently domain-general cognition 21 , 47 49 .…”
Section: Discussionsupporting
confidence: 88%
“…The ability to flexibly combine information in a domain-general manner 43 , when combined with playfulness and neophilic exploration of the environment, may be an important driver of technical innovations in kea and other species 44 , 45 . These results therefore support recent claims that tool use, including tooling, arises not only from the evolution of specialized physical cognition 46 49 , but can be innovated, when ecologically necessary, by species with sufficiently domain-general cognition 21 , 47 49 .…”
Section: Discussionsupporting
confidence: 88%
“…However, there might be an alternative hypothesis explaining the differences between Tool set and Sequential tool use: the low ATU and Correct success rates in the Sequential tool use rates could be explained by the fact that both tasks consisted of two separate apparatuses, which might have been an additional source of difficulty for the children. Yet there is no evidence in the literature that the use of (spatially separate) apparatuses or platforms poses an additional cognitive demand in tool use tasks for non-human animals or children (Gruber et al, 2019 ; Jackson, 1942 ; Martin-Ordas et al, 2012 ; Miller et al, 2020 ; Mulcahy et al, 2005 ; Warden et al, 1940 ). Experiment 2 controlled for the number of apparatuses (using a single apparatus for both ATU versions) and found that Tool set and Sequential tool use did not differ in either ATU nor Correct success rates.…”
Section: Discussionmentioning
confidence: 99%
“…All birds participated in various experiments before the presented study [ 31 33 ]. The training specifically required for the current study are tool use training, tool selection training, apparatus functionality training, hook training and tool transport training, five choice tool functionality training, and the temporal sequence training, which is outlined in the description of Conditions 1 and 2.…”
Section: Methodsmentioning
confidence: 99%